2011
DOI: 10.1074/jbc.m110.189175
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Cross-reactivity to Neutralize Two Different Scorpion Venoms with One Single Chain Antibody Fragment

Abstract: We report the optimization of a family of human single chain antibody fragments (scFv) for neutralizing two scorpion venoms. The parental scFv 3F recognizes the main toxins of Centruroides noxius Hoffmann (Cn2) and Centruroides suffusus suffusus (Css2), albeit with low affinity. This scFv was subjected to independent processes of directed evolution to improve its recognition toward Cn2 (Riaño-Umbarila, L., Juárez-González, V. R., Olamendi-Portugal, T., Ortíz-León, M., Possani, L. D., and Becerril, B. (2005) FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 47 publications
2
46
1
Order By: Relevance
“…Indeed, Am venom molecules (F3 fraction) could be detected easily by both, monospecific NbAahI'F12 and the bispecific NbF12-10 construct, which is suggestive for the presence of AahI related toxins or epitopes within the F3 fraction of Am venom. Similar results reported that human single chain fragment (scFv) recognized toxins of Centruroides noxius Hoffmann and Centruroides suffuses scorpion venom and rescue mice from severe envenomation by whole venom of Centruroides suffuses and Centruroides noxius [65]. Also, polyclonal anti-venom against Hadruroides lunatus displayed cross reactivity with venom from Tityus serrulatus, Centruroides sculpturatus and Androctonus australis hector scorpions [66].…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, Am venom molecules (F3 fraction) could be detected easily by both, monospecific NbAahI'F12 and the bispecific NbF12-10 construct, which is suggestive for the presence of AahI related toxins or epitopes within the F3 fraction of Am venom. Similar results reported that human single chain fragment (scFv) recognized toxins of Centruroides noxius Hoffmann and Centruroides suffuses scorpion venom and rescue mice from severe envenomation by whole venom of Centruroides suffuses and Centruroides noxius [65]. Also, polyclonal anti-venom against Hadruroides lunatus displayed cross reactivity with venom from Tityus serrulatus, Centruroides sculpturatus and Androctonus australis hector scorpions [66].…”
Section: Discussionsupporting
confidence: 66%
“…1A) that exclusively binds and modifies the gate functions of the human sodium channel Nav1.6 (11). We were able to obtain the scFv LR after three cycles of directed evolution of the parental scFv 3F and incorporating a V101F mutation into one of the derived variant scFvs (9004G) (12) (Fig. 1B).…”
mentioning
confidence: 83%
“…The scFv C1 variants were generated using strategies described previously (12,13) and those described in this study. We learned that only a few changes were required to obtain scFvs that neutralize the Cn2 and Cll1 toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinctive pharmacological properties are accompanied by distinctive immunological properties, as illustrated by the total absence of cross-reactivity between the ␣-and ␤-toxin classes (65). Moreover, unlike ␣-toxins, the ␤-toxins share greater structural homologies, as exemplified by significant cross-reactivity of a serum raised against a Centruroides immunogen with the main toxin from another Centruroides species (67,68). Hence, the availability of a crystal structure for a ␤-toxin bound to an antibody fragment is more likely to provide a canonical template for studying immunoreactivity of diverse members in this class of toxins than it is for ␣-toxins.…”
Section: Chemical and Functional Quality Of Fab4c1 And Fab9c2-mentioning
confidence: 99%